Women's Schooling and Religious Mobility: Joining, Switching, and Quitting Church in a Christian Sub-Saharan Setting. (10th July 2017) - Agadjanian, Victor
Abstract: In dialogue with mainly western literature on determinants of religious mobility and the evidence on the transformative role of mass education in developing settings, I examine the relationship of educational attainment with religious reaffiliation and disaffiliation in the context of rural and small-town sub-Saharan Africa. Adapting western scholarship to the realities of that context, where most people do not complete primary school, I conceptualize both basic education and religious belonging as parts and expressions of profound societal transformations in the sub-continent. I use data from a survey of women aged 18–50 years conducted in a predominantly Christian area in Mozambique to test this relationship from both the lifetime and dynamic perspectives. I find a strong positive association between educational level and the probability of church switching, with modest variations by denominational destination of and main reasons for reaffiliation. Disaffiliation is negatively related to schooling level. These findings are situated within a broader discourse on religion, development, and social change in the sub-Sahara.